Penggunaan Konseling Islam dalam Penanganan Ombrophobia pada Siswa: Sebuah Tinjauan Konseptual - Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2023)
The aims of this research is to describe the concept of Islamic counseling in dealing with ombrophobia in students. By using a literature study, research findings in the form of Islamic counseling are all types of efforts made to provide assistance to individuals to return to their natural state, and are able to develop and empower all the thoughts, faith and will that Allah SWT has given them, especially in overcoming ombrophobia, namely fear. too much rain. In its use, the steps taken start from problem identification, diagnosis, prognosis, therapy, and end with evaluation.